Medicinal preparations based on prickly artichoke (Cynara scolymus L.) (Texas Journal of Agriculture and Biological Sciences, 2022)
The basis of the article is the herbal medicinal raw material, the prickly artichoke Cynara scolymus L., belonging to the family (Asteraceae Dumort).